Nerve degeneration within the dental pulp after segmental osteotomies in the baboon (Papio ursinus) - Lownie, J. F.; Cleaton-Jones, P. E.; Fatti, L. P. (My University, 1996)
Following dentofacial surgical procedures, teeth in segments often do not sense thermal or electric stimuli. This study was undertaken to assess changes in the neural component of the dental pulp after posterior maxillary and mandibular segmental osteotomies, with or without interpositional autogenous bone grafting, in 26 Chacma baboons. Innervation was assessed histologically immediately after operation, and at 3, 6, 12 and 18 months. Statistically significant differences were present between the experimental and control groups. Even after 18 months no nerves were present in any of the mandibular teeth. In maxillary teeth, 50 per cent had demonstrable nerves in the graft group and 40 per cent in the no graft group. As nerve degeneration was present in the experimental teeth, patients should be warned of possible change in tooth sensibility, following these operations. Careful post-operative follow up for long periods in humans following dentofacial surgical procedures is thus essential.
KIM
Keywords: Dental Pulp; Nerve Degeneration; Papio; Osteotomy